Case Report: Typhoid Fever Complicated by Ileal Perforation in an Urban Slum of Dhaka, Bangladesh - Khanam, Farhana (Am J Trop Med Hyg, 2021)
Intestinal perforation is one of the most dangerous complications of typhoid fever and demands urgent hospitalization, diagnosis, and surgical management to reduce morbidity and prevent mortality. Here, we report a case of typhoidal intestinal perforation in a 19 year-old young man detected by passive surveillance during a cluster-randomized trial with Vi-tetanus toxoid conjugate vaccine (Typhoid Vaccine Acceleration Consortium: TyVAC) in an urban slum area in Mirpur, Dhaka, Bangladesh. The patient presented with a high-grade fever, lower abdominal pain, and vomiting and was admitted to a healthcare facility. Physical examination and preoperative investigations of the patient suggested a presumptive diagnosis of intestinal perforation, and the patient was transferred to a tertiary-level hospital for surgical management. A positive blood culture, intraoperative findings, and histopathology of an intestinal biopsy confirmed ileal perforation due to typhoid fever. This case report highlights the need for prompt diagnosis and appropriate pre- and postoperative management of patients who appear with the symptoms of typhoidal intestinal perforation. This report further demonstrates the importance of systematic surveillance and proper evaluation to determine the true incidence rate of typhoid fever and intestinal perforation in Bangladesh.